Propose a model of continuance intention to use IoT smart home in Malaysia - Hussin, Siti Farah; Abdollah, Mohd Faizal; Ahmad, Ibrahim (Little Lion Scientific Islamabad Pakistan, 2023)
The Internet of Things technology for smart home (IoTsh) are homes equipped with communication networks, systems, and sensors that can be used for controlling, monitoring, and scheduling enabling hardware IP devices according to user needs. The use of IoTsh can improve self-management, improve social care systems, and provide a better lifestyle. Although there are many IoTsh advantages, existing studies only focus on IoTsh acceptance and adoption. Nevertheless, studies regarding the intention to continually use IoTsh remain scarce, which calls for further investigation. To address this gap, this study proposes an integrated model for the purpose of understanding the intention of continuous usage of IoTsh among Malaysian users, as well as for investigating factors that impact or prevent the continuance intention of using IoTsh. The model combines three information system theories as the underlying theories, namely the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), Expectation-Confirmation Model (ECM), and Hofstede’s theory. The proposed model provides important insights for IoTsh providers, manufacturers and governments on continuance intention to use IoTsh, understanding the users' desires and subsequently designing their services.